Taking a New Look at MaineCare - Saucier, Paul (Maine Policy Review, 2007)
Maine’s Medicaid program, called MaineCare, provides health care coverage to one in five state residents. Paul Saucier gives an overview of MaineCare’s services, eligibility categories, and financing. He discusses root causes of MaineCare’s continued expansion in breadth and cost, which has prompted reform proposals to rein in what many believe is unsustainable growth. Examining reform efforts in other states, Saucier cautions that we need to learn from these experiments. Finally, he raises important questions for policymakers related to MaineCare’s mission, its complexity, and the stability of its financing.